Experimental studies using reagents softeners for getting water coal suspension from shubarkul coal’s slimes - Kussaiynov, K.; Alpysova, G.K.; Tanashev, E.T.; Tolynbekov, A.B.; Tleubergenova, A. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Modern development of power system is characterized by the reduction of share of an expensive liquid fuel use which is a valuable raw material for the refining industry and the increasing use of solid fuels. Stockpiles of high coal deposits are depleted due to the increase share of solid fuels. Furthermore, there is deterioration in the quality of solid fuels extracted by mining method. The transition to the development of powerful coal fields mined in the open way and its use as a fuel for power plants and other fuelusing devices are connected with certain difficulties. The main reason is high cost and power consumption of preparatory process in burning.
Keywords: Shubarkul coal’s slimes; coal-water slurries; reagent-weight plasticizer; sodium humate; oil